Farm models and economic valuation in the context of multifunctionality: a review of approaches from France, Germany, The Netherlands and Portugal. (26th August 2008) - Zander, Peter; Groot, Jeroen C.J.; Josien, Etienne; Karpinski, Isabella; Knierim, Andrea; Meyer, Burghard; Madureira, Livia; Rambonilaza, Mbolatiana; Rossing, Walter
Multifunctionality of Agriculture (MFA) is a concept that supports the recognition of complex interdependencies between different resources, production processes and outputs of agricultural land use. Political decision making within a sustainable development frame requires extensive information about these interrelationships in order to analyse the impact of implemented policies and to assess future policy effects. This paper presents selected results of the EU FP6 supported MultAgri project, such as a comparative overview of models, techniques and tools that have been applied to the assessment of various agricultural outputs. In detail, multidimensional modelling tools and economic valuation instruments have been inspected and valuated. Examples from France, Germany, The Netherlands and Portugal – the countries reviewed within the MultAgri workpackage 3 – are used to highlight specific instrumental strengths and weaknesses. Conclusions are drawn with respect to further methodological research needs on multifunctionality of agriculture.